MENGHADIRKAN FILM DALAM PEMBELAJARAN BAHASA `JERMAN SEBAGAI BAHASA ASING (DEUTSCH ALS FREMDSPRACHE) - Dwi Imroatu Julaikah (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2017)
German language is taught in Indonesia as a foreign language, or we usually call as DAF (Deutsch als Fremdsprache). This language is taught in formal and non-formal institutions. In this context, it is very important, especially for the teacher to bring interactive and joyfull learning in the classroom, and it is challenging for the teacher. Thus, presenting interesting language in the class, full of innovativation in learning prosess of German language, must be done. One of the choices to get those situations in the classroom is to bring a good media. Film is one alternative that can be presented. This paper discusses how to bring movies in learning a foreign language (German). Further discussion is more about (a) Definition of film, (b) Film, as a medium in teaching learning process, and (c) How to teach German with didactic and methodic in learning German language.